PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MUATAN IPS MENGGUNAKAN APLIKASI CAPCUT DI KELAS V SDN 01 KOTO BARU - Yulia Darniyanti; Muhammad Subhan; Yuliska Hoiriyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Theresearch was motivated by several problems, including first, the difficulty of teachers developing animated learning video media, especially for social studies learning of Geography characteristic material in Indonesia, second, teachers find it difficult to develop media in schools, third, students are less interested in the learning process, especially social studies content because social studies learning contains many theories. One effort that can attract the attraction of students is done by developing animated video learning media that can support students to learn well. Therefore, the author is interested in developing animated video learning media using the CapCut application in elementary schools. With the aim that teachers and students have enough adequate learning media. The type of research is research and development (R&D). Research and Development is a process and research steps to develop existing products, as well as new products that can later be accounted for. Develop a product a learning video. Research and development (R&D) Research and Development (R&D) methods are used to produce a particular product and tested for effectiveness. The development model used is the development of ADDIE " This ADDIE model was chosen because one of the teaching material development designs that are often used inthe development of ADDIE has 5 parts that are interconnected with one another: Analysis Stage, Design (Planning), Development Stage (Development), tahap Implementation, tahap Evaluation. Halil from the research of validation of animated video media of geographical characteristics material in Indonesia in class V in the validation test by two expert validators. Language validation by 80.00% lecturers falls into the very valid category. Media validation by 93.33% lecturers falls into the very valid category. Material validation by lecturers is 90.00% included in the very valid category.